Role of prevention and screening in epithelial ovarian cancer - Rani, Peddireddi Reddi; Reddy, Kanipakapatnam Sathyanarayana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Epithelial ovarian carcinoma is a disease with poor prognosis and high mortality among gynaecological cancers due to inaccessibility of ovary for inspection or sampling and lack of proper screening methods. Strategies to detect early ovarian cancer include estimation of serum CA-125 and transvaginal ultrasound (TVS) for morphological index. Studies have shown that screening of asymptomatic average risk post-menopausal women did not show any benefit and are associated with false positive results which may lead to unnecessary surgery and resultant morbidity. The risks outweigh benefits. Present recommendation is to screen high risk women especially hereditary cancers and offer risk reducing surgery when needed. Prophylactic salpingectomy/oophorectomy may offer the opportunity to prevent ovarian cancer. More trials and more research in newer biomarkers are needed.